2017
DOI: 10.1007/s00253-017-8370-x
|View full text |Cite
|
Sign up to set email alerts
|

The recombinant fusion protein of cholera toxin B and neutrophil-activating protein expressed on Bacillus subtilis spore surface suppresses allergic inflammation in mice

Abstract: The neutrophil-activating protein of Helicobacter pylori (HP-NAP) has been identified as a modulator with anti-Th2 inflammation activity, and cholera toxin B (CTB) is a mucosal adjuvant that can also induce antigen tolerance. In this study, we constructed a CTB-NAP fusion protein on the surface of Bacillus subtilis spore and evaluate the efficiency of oral administration of the recombinant CTB-NAP spores in preventing asthma in mice. Oral administration of recombinant CTB or CTB-NAP spores significantly decrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 43 publications
3
19
0
Order By: Relevance
“…As FSM can reduce IgE synthesis and increase IgG synthesis, it can shift the Th1/Th2 balance toward Th1 by regulating B cells to produce IgG instead of IgE. Dong et al . also found that the allergen‐specific IgG2a and IFN‐ γ increased and IgE levels decreased after the immunomodulating properties of the antigen were modified.…”
Section: Resultssupporting
confidence: 92%
“…As FSM can reduce IgE synthesis and increase IgG synthesis, it can shift the Th1/Th2 balance toward Th1 by regulating B cells to produce IgG instead of IgE. Dong et al . also found that the allergen‐specific IgG2a and IFN‐ γ increased and IgE levels decreased after the immunomodulating properties of the antigen were modified.…”
Section: Resultssupporting
confidence: 92%
“…Peanut allergy is an IgE‐mediated food allergy that can cause an increase in IL‐4, IL‐5 and IL‐13 expression . Our previous study indicated that CNAP spores could inhibit OVA‐induced asthma and reduce IL‐4 and IL‐5 expressions in a murine model . In the present study, recombinant NAP or CNAP spore treatment reduced IL‐4 and IL‐5 expression and increased IFN‐γ expression in the spleen cells of peanut‐sensitized mice.…”
Section: Discussionsupporting
confidence: 58%
“…Bacillus subtilis spore coat protein C (B.s-CotC), B.s-CotC-CTB, B.s-CotC-NAP and B.s-CotC-CNAP were constructed according the protocol mentioned in our previous study. 11,14 Recombinant spores were cultured in Difco sporulation medium (DSM; BD Biosciences). After incubation with shaking at 250 rpm for 24 hours, spores were harvested by centrifugation at 8000 g for 10 minutes and then treated with 4 mg/ mL lysozyme at 35°C for 30 minutes to disrupt residual sporangial cells.…”
Section: Spore Preparationmentioning
confidence: 99%
See 2 more Smart Citations